Adult ADHD: A Narrative Review of Symptoms, Assessment, and Intervention Strategies - Farra Anisa Rahmania; Dwi Fadhila (Faculty of Psychology Universitas Gadjah Mada, 2026)
Attention-Deficit/Hyperactivity Disorder (ADHD) is recognized as a neurodevelopmental condition that persists across the lifespan; however, research focusing on adults with ADHD has received comparatively less attention than studies in children. This narrative literature review aims to explore recent evidence on adult ADHD, with particular emphasis on symptoms, functional impacts, and intervention strategies. Relevant literature was identified through a targeted search of selected databases, guided by an Integrative Review Framework (IRF). The review focused on peer-reviewed publications from 2020 to 2025 involving adult populations diagnosed with ADHD. The findings suggest that ADHD symptoms in adults influence multiple domains of daily functioning, including difficulties in attention and organization that affect academic and occupational performance, challenges in interpersonal relationships, and an increased risk of psychological comorbidities such as mood disorders, anxiety, and behavioral problems. Various intervention approaches have been reported, including pharmacological treatment, cognitive-behavioral therapy, coaching strategies, and integrated models combining psychosocial and medical components. This review underscores the importance of improving the assessment of ADHD in adulthood, developing tailored interventions, and encouraging longitudinal research to better understand long-term outcomes, ultimately contributing to improved resilience and quality of life for adults with ADHD. Keywords: Adult ADHD; ADHD Symptom; ADHD Assessment, ADHD Intervention; Narrative Literature Review